The Application of Islamic Education Values through the End of Month Al-Qur'an Khatam Activity at BUQ Elementary School Betengan Demak - Musawamah, Mualamatul (International Journal on Advanced Science, Education, and Religion, 2025)
The monthly Al-Qur’an completion (khataman) activity at SD BUQ Betengan Demak is a routine program that plays a significant role in fostering students’ character and religious values. This study aims to describe the implementation of Islamic educational values—including faith (aqidah), worship (ibadah), and morals (akhlaq)—through the monthly khataman Al-Qur’an program at the elementary school. This research employs a descriptive qualitative method, with data collected through in-depth interviews with the principal, the Qiro’ati activity coordinator, and participating students. The findings indicate that the khataman Al-Qur’an is not merely a tradition of collective recitation, but also serves as a means of faith building through understanding the meaning of Qur’anic verses and instilling the pillars of faith by teachers and the activity coordinator. Additionally, the khataman activity effectively increases students’ enthusiasm for worship, both in Qur’an reading and other forms of worship at school and at home. The habituation of proper etiquette during the activity, such as sitting orderly, listening attentively, and showing respect toward teachers and peers, contributes to the development of noble character among students. This activity receives full support from the principal and teachers as an integral part of the school’s vision and mission to produce excellent, accomplished, and Qur’anic-mannered generations. Thus, the implementation of Islamic educational values through khataman Al-Qur’an at SD BUQ Betengan Demak has been proven effective in holistically strengthening the students’ spiritual and character development.